Consequences of Participating in Questionable Academia: A Global Survey of Authors of Journal Articles and Conference Presentations - Kulczycki, Emanuel; Rotnicka, Sara (My University, 2022)
We designed a survey to examine the consequences of publishing in predatory journals and presenting at questionable conferences. The response rate of 4.1% is low, but expected, primarily because of the sensitivity of the subject matter. Nevertheless, as we have shown by comparing the responses obtained from all presenters (Figure 1), the geographical distribution of the responses allows us to draw more general conclusions. The results deserve further analysis and presentation in an expanded form. In the next step, we plan to deepen the present quantitative analysis and cross reference it with a qualitative analysis of the more than 600 responses we obtained to the open questions. Our survey shows a positive effect for individual researchers related to the activities we asked about. This can be seen both in the fact that, if researchers obtained advice before submitting an article to a journal or conference, this advice was in favour of a given outlet. Reactions from the close academic scientific community, as well as reactions beyond it, show that many researchers were congratulated and felt that this publication/presentation had a positive impact on their work. However, it is important to note that 13.3% of respondents indicated that the publication/presentation we asked about was not considered in their evaluation and nine researchers were fired because of this publication/presentation. One of the objectives of our study was to emphasise the perspective of researchers who choose to cooperate with questionable journals or conference organisers. Although numerous previous studies have presented the harmful effects of predatory academia, the majority of respondents indicated positive consequences of their choice. Both the authors’ positive judgement regarding their papers’ impact on science, as well as the positive formal consequences of such a choice of publishers, may indicate that such papers can encourage the rethinking of academic policies. The prevalence of the phenomenon may suggest that it is profitable for many authors to function within the predatory academy. Nonetheless, besides profiting individuals, it is detrimental to the wider scientific community. Thus, it is crucial to encourage researchers to function within credible means of scholarly communication, which would meet not only their own specific needs but would also be advantageous for the scholarly community.
Keywords: predatory publishers; predatory jouranals; scholarly communication; motivations